Rancang Bangun Protokol Alternatif Saat Konektivitas Internet Terputus Pada Pertanian Berbasis IoT - Irham Fadilah; Endah Fitriani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
In the era of agricultural digitalization, dependence on Internet of Things (IoT) technology is increasing, yet supporting infrastructure remains vulnerable to connectivity disruptions. This research aims to develop an alternative protocol for IoT-based agricultural systems that can operate during internet connection failures, focusing on implementing a failsafe mode using NodeMCU ESP8266. The research methodology includes developing a monitoring system using soil moisture sensors and ultrasonic sensors for water level detection, as well as performance evaluation based on decision-making accuracy parameters, mode transition response time, and consistency in water management. Implementation results showed a 40,1% reduction in water consumption compared to traditional irrigation methods. The failsafe mechanism demonstrated sustained operations with 98% reliability in maintaining optimal soil moisture levels during 72-hour offline periods. This research contributes significantly to the development of smart agriculture through a cost-effective and scalable solution, particularly for areas with limited infrastructure that only require basic internet connectivity and minimal maintenance.